Effects of Obesity and Thrombophilia on the Risk of Abortion in Women Undergoing In Vitro Fertilization - Candeloro, Matteo; Di Nisio, Marcello; Ponzano, Adalisa; Tiboni, Gian Mario; Potere, Nicola; Tana, Marco; Rutjes, Anne W. S.; Porreca, Ettore (Frontiers in Endocrinology, 2020)
ntroduction: Obesity is associated with a higher risk of abortion in women undergoing in-vitro fertilization (IVF). Whether thrombophilia amplifies this risk is currently unclear. The aim of this study was to evaluate the effects of thrombophilia on the risk of abortion in obese women treated with IVF. Methods: Patient characteristics, presence of inherited or acquired thrombophilia, and comorbidities were prospectively collected before the procedure in consecutive women undergoing IVF. The primary outcome was the incidence of abortion among women who achieved a clinical pregnancy. Results: A total of 633 non-obese and 49 obese Caucasian women undergoing IVF were included. Two-hundred and four (32%) women achieved clinical pregnancy, of whom six had an ectopic pregnancy and 63 experienced an abortion, which occurred in 51 (80.9%) cases during the first 10 weeks of gestation. The incidence of abortion was substantially higher in obese women compared to non-obese women after adjusting for age (64.3% vs. 29.3%, odds ratio [OR] 4.41; 95% CI 1.41 to 13.81). Obese women with one or more thrombophilia seemed to have a higher risk of abortion compared to non-obese women with no thrombophilia (unadjusted OR 5.97; 95% CI 1.44 to 24.77). Abortion occurred during the first 10 weeks of gestation in 88.9% of obese women with one or more thrombophilia compared to 33.3% of obese women without thrombophilia, and 20.7% of non-obese women. Conclusions: Obese women undergoing IVF have a high risk of early abortion which seems further increased by the concomitant presence of thrombophilia.